Le fratture del femore prossimale in età pediatrica - Origo, C.; Toniolo, R.; Giusti, C.; Catena, N. (Lo Scalpello - Journal, 2018)
PROXIMAL FEMORAL FRACTURES IN CHILDRENProximal femoral fractures are rare in children; however, they are associated with a high rate of complications. Theyare the consequence of high energy trauma following motor vehicle accidents and falls from greater heights. The idealtreatment for displaced fractures should include anatomical reduction and stable fixation, if possible within 24 hoursfrom the trauma in order to reduce the incidence of sequelae. Adequate fixation may be obtained using Kirschnerwires, cannulated screws, plates and screws or external fixators, depending on the type of fracture. Complicationsinclude avascular necrosis of the femoral head, coxa vara, nonunion, premature physaeal closure and limbdiscrepancy.